Effectiveness of iodine derived from Eucheuma spinosum against the bacteria Staphylococcus aureus and Salmonella sp. - Apri Arisandi,; Farid, Akhmad; Wulandari, Rizka Ayu; Muktisari, Ratri Diah (JURNAL MINA SAINS, 2024)
Seaweed is the primary source of carrageenan, but it also contains iodine, which can inhibit bacterial activity and growth. The iodine contained in seaweed results from interaction with the marine environment rich in iodine. The research was conducted from June to November 2022 and used iodine from seaweed extraction to test antibacterial activity (Staphylococcus aureus and Salmonella sp). The antibacterial activity test was carried out for 48 hours. The iodine concentration was determined using titration, while the antibacterial activity test used the Disc Diffusion Test. The research showed that Eucheuma spinosum extract contained iodine, 0.38% - 1.22%. The antibacterial activity of seaweed iodine test results revealed an average inhibition zone diameter of 11.5 mm for Staphylococcus aureus and 12 mm for Salmonella sp. This research shows that the iodine in Eucheuma spinosum extract has an inhibitory solid impact on the activity and growth of Staphylococcus aureus and Salmonella sp.